Effects of airborne Aspergillus on serum aflatoxin B1 and liver enzymes in workers handling wheat flour. (January 2016) - Saad-Hussein, A; Taha, MM; Fadl, NN; Awad, A-H; Mahdy-Abdallah, H; Moubarz, G; Aziz, H; El-Shamy, KA
Objective: The present work aimed to investigate the relationship between occupational exposure to airborne molds, serum aflatoxin B1 (AFB1 ), and liver enzymes of workers handling wheat flour. Methods: The study included 90 bakers, 100 flour milling workers, and 100 controls with no exposure to flour dust. Workplace aspects such as temperature and relative humidity were measured. Airborne fungi were collected and identified. In all subjects included, the serum levels of AFB1, serum albumin (Alb), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) were measured. Results: Air temperature and relative humidity were found to be higher in bakeries than in flour mill sections. Airborne Aspergillus species were isolated in dust particles <8 µm in size. The concentration of Aspergillus flavus and Aspergillus niger were higher in bakeries than in the flour mill sections. They were higher in the grinding section than in other mill sections. The serum AFB1 -Alb adduct and ALP levels were significantly higher in bakers compared to milling workers ( p < 0.0001, p = 0.05), respectively. The liver enzymes AST and ALT were significantly higher among milling workers and bakers than controls ( p < 0.05, p < 0.0001), respectively. The duration of exposure was significantly correlated with serum AFB1 in bakers. Moreover, there was significant correlation between serum AFB1, each of ALT and AST levels in bakers. Conclusions: chronic occupational exposure to high concentrations of Aspergillus in workplaces may cause elevations in serum levels of AFB1 and liver enzymes in workers exposed to flour dust. Hence, worker protection measures should be consistently adopted and enforced at the workplace.